2017
DOI: 10.1093/annonc/mdx486
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cigarette consumption predict mortality in patients with head and neck cancer: a pooled analysis within the International Head and Neck Cancer Epidemiology (INHANCE) Consortium

Abstract: BackgroundThis study evaluated whether demographics, pre-diagnosis lifestyle habits and clinical data are associated with the overall survival (OS) and head and neck cancer (HNC)-specific survival in patients with HNC.Patients and methodsWe conducted a pooled analysis, including 4759 HNC patients from five studies within the International Head and Neck Cancer Epidemiology (INHANCE) Consortium. Cox proportional hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) were estimated including ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
85
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 23 publications
1
85
2
1
Order By: Relevance
“…In that study, subgroup analysis revealed that the addition of cetuximab led to a trend toward improved outcomes in young patients, those with HPV-negative tumors of the oropharynx or hypopharynx, and the T4 subgroup. [28][29][30][31] National Comprehensive Cancer Network guidelines recommend 3-weekly or weekly cisplatin as standard treatment options. Seventy percent of patients in that study had primary tumors in the oropharynx, and only 27% of these were HPV-negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, subgroup analysis revealed that the addition of cetuximab led to a trend toward improved outcomes in young patients, those with HPV-negative tumors of the oropharynx or hypopharynx, and the T4 subgroup. [28][29][30][31] National Comprehensive Cancer Network guidelines recommend 3-weekly or weekly cisplatin as standard treatment options. Seventy percent of patients in that study had primary tumors in the oropharynx, and only 27% of these were HPV-negative.…”
Section: Discussionmentioning
confidence: 99%
“…9,24-27 Furthermore, our patients had a high proportion of hypopharyngeal primaries, high rates of tobacco use (86.5%), and almost one-fifth had gross perinodal extension, all of which are recognized adverse prognostic features. [28][29][30][31] National Comprehensive Cancer Network guidelines recommend 3-weekly or weekly cisplatin as standard treatment options. 32 We used weekly cisplatin in this study, and it is used worldwide, especially in head and neck cancer-endemic regions (>85% of centers), at doses from 30 to 40 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…21 On the other side, the possible relation between cancer and glycemic metabolism represents a new field of interest. 21 On the other side, the possible relation between cancer and glycemic metabolism represents a new field of interest.…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…The relationship between alcohol and tobacco with head and neck cancer is well known, with a synergic risk in case that both are abused of. 21 On the other side, the possible relation between cancer and glycemic metabolism represents a new field of interest. Recent studies have pointed out that insulin resistance in patients with head and neck cancer might be an important prognostic indicator.…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…Prediagnosis cigarette smoking can be a prognostic factor for overall survival (OS) in OSCC patients (4). Therapeutic options for early stage OSCC include both surgery and radiotherapy as single treatment modality, while those for advanced stage include surgery, chemoradiation and chemotherapy (5,6).…”
mentioning
confidence: 99%